Ancaman Pemiskinan Perempuan Miskin Kota Pelaku Usaha Mikro Dan Kecil dalam Pembayaran Digital: Studi Kasus Bidara Cina, Jakarta Timur - Nathania Yunita Dharma; Hariati Sinaga (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
The informal economy is a common economic activity in Indonesia. Participation in the informal economy is predominantly carried out by women, particularly those belonging to the urban poor. This study aims to fill the research gap regarding the adaptation of women entrepreneurs to digital payments by using Naila Kabeer's Gender and Poverty Theory as an analytical tool that generally highlights the process of poverty that is closely related to gender relations and positions women as an adjustment variable in the poverty trap. This study uses a qualitative research approach with a case study research type. Data collection was conducted through in-depth interviews with two informants who are also micro and small business owners in Bidara Cina with two different characteristics: business owners who provide cashless transactions and business owners who do not provide cashless transactions. The results show that women entrepreneurs have the burden of reproductive responsibilities as well as being business owners, which places women in a subordinate position as well as an adjustment variable in the family economy. The burden of domestic work and care affects the running of businesses carried out by women entrepreneurs. The condition of women as entrepreneurs is also increasingly vulnerable due to limited access and control over resources, knowledge, and service systems in the digital economy, which makes it difficult for women micro and small business owners. Digital economic policies also cause shocks due to the unpreparedness of women entrepreneurs to adapt due to various multidimensional problems that further strengthen the unequal position of women in the economy, especially in the digital economy.